Comparative Study of Flunarizine versus Propranolol in the Prophylaxis of Migraine (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Propranolol and flunarizine are the most used first-line drugs in the treatment of migraine. There are limited data regarding the use of prophylactic agents available in Bangladesh. This study aimed to compare the efficacy and tolerability of propranolol and flunarizine in prophylactic management. Materials and methods: This was a open label randomized clinical trial. One hundred and fifty migraine patients were recruited from the Outpatient Department of Neurology and Medicine of Chittagong Medical College Hospital from October, 2017 to September, 2018. They were randomized in a 1:1 ratio to receive either flunarizine (n=75) or propranolol (n=75) once daily. Patients were evaluated for attack frequency, pain severity, duration of headache, disability and drug side effects at 6 weeks and 12 weeks. Results: The Flunarizine group showed a reduction in the mean (±SD) frequency of migraine attacks from 10.58±4.11 to 3.25±2.90 per month, intensity of headache per attack from 8.00±1.33 to 3.63±1.87, number of headache days per month from 11.93±4.12 to 3.25±2.90, duration of headache per episode from 21.18±16.15 to 3.13±3.26 and MIDAS (Migraine Disability Assessment Test) score from 23.15±8.77 to 4.70±4.80. In patients treated with propranolol, a reduction in the mean (±SD) of monthly frequency of migraine attacks from 9.64±3.81 to 4.67±3.15, the intensity of headache per attack from 7.99±1.27 to 4.57±1.48, number of headache days per month from 11.66±4.49 to 4.67±3.15, duration of headache per episode from 24.19±19.33 to 4.85±4.31 and MIDAS score from 23.78±10.48 to 6.51±5.36. The percentage of responders at the study endpoint was 58.2% for propranolol and 80.3% for flunarizine. Both the drugs were well tolerated but adverse effects were more in the propranolol group. Conclusion: Flunarizine was more effective and better tolerable than propranolol in prophylaxis of migraine.Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 24-28